Self-administered active versus sham acupressure for diarrhea predominant irritable bowel syndrome: a nurse-led randomized clinical trial - Maha Gamal Ramadan Asal; Ahmed Abdelwahab Ibrahim El-Sayed; Samira Ahmed Alsenany; Zahraa Hassan Ramzy; Rasha Fathy Ahmed Dawood (BMC Nursing)
Abstract Background Diarrhea-predominant irritable bowel syndrome (IBS-D) significantly impacts patients’ quality of life, with existing treatments offering limited relief. Self-administered acupressure presents a potential non-invasive, cost-effective treatment option that could alleviate symptoms and enhance health outcomes in these patients. Aim This randomized controlled trial aimed to evaluate the effect of active acupressure compared to sham acupressure on primary and secondary outcomes among IBS-D patients. Method The study included 63 patients with IBS-D, recruited from Alexandria Main University Hospital, Egypt. Participants were randomized into either an active acupressure group or a sham acupressure group. Both groups underwent two days of training, followed by four weeks of intervention. The active group applied pressure to specific therapeutic acupoints, while the sham group used non-therapeutic points. Outcomes were assessed at baseline, week 2, and week 4. Results The active acupressure group showed a significant reduction in symptom severity, improved stool consistency, and frequency, and greater adequate symptom relief by week 4 compared to the sham group. Psychological outcomes, including anxiety and depression, also improved significantly in the active group. Additionally, the active group reported reduced use of rescue medications. Conclusion Active acupressure is an effective nursing intervention for alleviating symptoms of IBS-D, particularly when applied consistently over time. It improves both physical and psychological outcomes, offering a valuable non-pharmacological treatment option. Implications Nurses can integrate self-administered acupressure into IBS-D care plans, teaching patients this technique to manage symptoms independently, thus enhancing their quality of life (QOL) and reducing reliance on conventional medications. This intervention aligns with holistic nursing care and offers a cost-effective, patient-friendly solution for managing IBS-D. Trial registration This study was prospectively registered as a randomized controlled trial in https://clinicaltrials.gov/ Registration Date: January 7, 2023, Registration Number: NCT05702255.